S32 Loss/inhibition of the aVb5 integrin reduces allergen-induced increases in airway smooth muscle mass in in vivo models of asthma. (2nd December 2011) - Tatler, A L; John, A E; Jolly, L; Habgood, A; Porte, J; Knox, A J; Huang, X; Sheppard, D; Jenkins, G
Abstract : Airway remodelling is a common feature of severe asthma. Transforming growth factor-ß (TGF-ß) is a pro-fibrotic, pleiotropic cytokine implicated in airway remodelling. TGF-ß is sequestered in the extracellular matrix as a latent complex and requires activation to function. We have previously shown that contraction agonists cause aVß5-mediated TGF-ß activation by human airway smooth muscle cells. The study aims were to investigate the role of the aVß5integrin in airway remodelling in vivo using two distinct mouse models of asthma. A blocking antibody directed against the aVß5 was used in the ovalbumin (OVA) model of asthma. Mice were sensitised with OVA/Alum on days 0 and 12, then challenged byoropharyngeal administration of OVA 10 times over 2 weeks. The anti-aVß5antibody or an isotype matched control antibody was administered for the duration of the OVA challenges. The second invivo model utilised itgb5 −/− mice. Aspergillous fumigatus antigen preparation was administered intra-nasally (10 μg/mice) to itgb5 −/− and wild type controls 9 times over a 21-day period. a-Smooth muscle actin (a-SMA) was quantified in lung sections from both studies by immunofluorescence. Murine airway smooth muscle cells express aVß5 integrin and can activate TGF-ß in vivo in response to allergen challenge as measured by αvβ5 and phospho-Smad2 immunostaining. Treatment with both OVA and Asp.f resulted in an increase in a-SMA staining around the smaller airways. The aVß5blocking antibody significantly reduced a-SMA staining compared with the isotype control antibody. Furthermore, itgb5 −/− mice had significantly less a-SMA around their airways than wild type control mice in response to Asp.f treatment. However, both itgb5 −/− andanti-aVß5 treated mice had significantly more airway inflammation and more inflammatory cells present in the bronchoalveolar lavage compared with their matched controls. These data provide evidence that airway smooth muscle cells can activate TGF-ß in vivo. Inhibition of, or genetic loss of, the aVß5 integrin significantly reduces allergen-induced increases in airway smooth muscle mass, however, peribronchial inflammation is increased consistent with the known effects of TGFβ. Targeted inhibition of the aVß5 integrin may reduce airway remodelling, but global inhibition is unlikely to be useful due to the enhanced inflammatory response.